Detecting trends in seagrass cover through aerial imagery interpretation: Historical dynamics of a Posidonia oceanica meadow subjected to anthropogenic disturbance - Gianluca Mancini; Gianluca Mastrantonio; Alessio Pollice; Giovanna Jona Lasinio; Andrea Belluscio; Edoardo Casoli; Daniela Silvia Pace; Giandomenico Ardizzone; Daniele Ventura (Ecological Indicators, 2023)
Over the last century, P. oceanica meadows have undergone significant regression along Mediterranean coasts due to anthropogenic disturbances. Using an integrated approach based on historical aerial photography interpretation in GIS environment and Bayesian modelling, we mapped the upper limits of a P. oceanica meadow and identified the most influential disturbance factors acting along the coast of Giglio Island, where several local human-mediated impacts have historically co-occurred from 1968 to 2013. Model selection based on the DIC criterion suggested that the presence of the impacts is suitable for describing the seagrass coverage variation. Similarities in P. oceanica cover within 13 investigated zones were highlighted when considering the most relevant impacts, such as harbour expansion, mining, and anchoring. The detected adverse effects indicate the need for implementing management actions focusing on the present and past sources of impact to reduce their effect on P. oceanica beds actively.